Syntheses and Spectroscopic Studies on Macrocyclic Complexes of Dioxomolybdenum(VI) with Furil as Precursor - D. P. Rao; H. S. Yadav; A. K. Yadava; Sanjay Singh; U. S. Yadav (E-Journal of Chemistry)
Due to their biological relevance, molybdenum catalyzed oxygen transfer reactions have great interest. With this view, some dioxomolybdenum(VI) complexes with general formula [MoO2(mac)](acac)2, (where mac = tetraazamacrocyclic ligands derived from condensation of furil with 1,2-ethanediamine or 1,3-propanediamine and their reaction with β-diketones) have been synthesized using dioxometal ion as kinetic template. The prepared complexes have been characterized by electrical conductance, elemental analyses, infrared and electronic data. All the dioxomoly-bdenum(VI) complexes have octahedral geometry with six coordination.